The role of Peruvian women inventors in technological development: Analysis of their patent production - Karen Esteincin, Cuba Vargas; Vanessa Yaniz, Palomino Monteza; Néstor Bernardo, Corpus Vergara (LACCEI, 2025)
The role of Peruvian female inventors in technological development is reflected in their growing participation in patent creation, highlighting the importance of gender equity in innovation despite structural and cultural barriers that hinder their access to technological and financial resources. In 2022, 74 patent applications by women were recorded, primarily for utility models, while invention patents remain less common due to their greater complexity. Public policies have been essential in promoting female inclusion, but these measures need to be strengthened to address persistent inequalities and achieve greater equity in scientific and technological fields.